2018
DOI: 10.1038/s41598-018-23702-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying extracellular matrix turnover in human lung scaffold cultures

Abstract: Remodelling of the extracellular matrix is accomplished by altering the balance between matrix macromolecule production and degradation. However, it is not well understood how cells balance production of new matrix molecules and degradation of existing ones during tissue remodelling and regeneration. In this study, we used decellularized lung scaffolds repopulated with allogenic lung fibroblasts cultured with stable isotope labelled amino acids to quantify the balance between matrix production and degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 58 publications
(65 reference statements)
3
55
0
Order By: Relevance
“…In a previous long-term study (6 weeks) in human bronchial epithelial cells, it was observed that AgNPs induced pro-fibrotic responses at both gene and protein level, such as increased collagen deposition and epithelial-mesenchymal transition [ 6 ]. In the present study, we could not detect any major changes in ECM synthesis of either proteoglycans (except at 72 h exposure of Ag10, 2 µg/mL) or total amount of collagens by fibroblasts, which are vital components in ECM homeostasis [ 8 ]. However, we analyzed the total amount of soluble proteoglycans and collagens which could be discriminated if changes were present on individual ECM proteins.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a previous long-term study (6 weeks) in human bronchial epithelial cells, it was observed that AgNPs induced pro-fibrotic responses at both gene and protein level, such as increased collagen deposition and epithelial-mesenchymal transition [ 6 ]. In the present study, we could not detect any major changes in ECM synthesis of either proteoglycans (except at 72 h exposure of Ag10, 2 µg/mL) or total amount of collagens by fibroblasts, which are vital components in ECM homeostasis [ 8 ]. However, we analyzed the total amount of soluble proteoglycans and collagens which could be discriminated if changes were present on individual ECM proteins.…”
Section: Discussionmentioning
confidence: 86%
“…Upon damages of the airway epithelial cell layer due to chronic lung disease or chronic exposure of inhaled particles, cells beneath the epithelial basement membrane will become exposed to nanoparticles, triggering an inflammatory response that may promote locally enhanced levels of pro-inflammatory cytokines. Fibroblasts are mesenchymal cells, crucial for maintaining homeostasis of ECM proteins, such as collagens and proteoglycans, components that together act as important reservoirs for cytokines and growth factors [ 8 , 9 ]. The ECM provides steady, elastic and durable walls of the alveoli, which are necessary for breathing efficiently and creating low resistance for gas exchange.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of composition of extracellular matrix on nasal polypoid tissues' mechanical properties has been previously demonstrated [10,12,33], but the role of nasal polypoid cells in this mechanical dysfunction continues to remain unclear. In this context, the fibroblasts act in the tissue remodeling and amplification of inflammation through extracellular matrix-cell cross-talking [36,37], act on the pillars of nasal polyp development [38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the execution of the SOLAµ TM HRP spin plate workflow still requires a certain degree of operator handling and represents only a semi-automatic platform, nevertheless, it provides a higher degree of standardization and reproducibility than the manual ZIPTIP ® C18 pipette tip workflow. However, due to the semi-automatic system properties and the consequent compatibility with LC-MS-based high-throughput screening strategies, centrifugal SPE spin plates have recently been “expected to become the mainstream method of sample processing in the future” [36] and were successfully used in various proteomic study designs focusing on human cerebrospinal fluid [37], human serum [38], human lung tissues [39] and HeLa cells [40].…”
Section: Discussionmentioning
confidence: 99%